Evolutionary and environmental determinants of freshwater fish thermal tolerance and plasticity - Lise Comte; Julian D. Olden (Global Change Biology, 2017)
Understanding the extent to which phylogenetic constraints and adaptive evolutionary forces help define the physiological sensitivity of species is critical for anticipating climate‐related impacts in aquatic environments. Yet, whether upper thermal tolerance and plasticity are shaped by common evolutionary and environmental mechanisms remains to be tested. Based on a systematic literature review, we investigated this question in 82 freshwater fish species (27 families) representing 829 experiments for which data existed on upper thermal limits and it was possible to estimate plasticity using upper thermal tolerance reaction norms. Our findings indicated that there are strong phylogenetic signals in both thermal tolerances and acclimation capacity, although it is weaker in the latter. We found that upper thermal tolerances are correlated with the temperatures experienced by species across their range, likely because of spatially autocorrelated processes in which closely related species share similar selection pressures and limited dispersal from ancestral environments. No association with species thermal habitat was found for acclimation capacity. Instead, species with the lowest physiological plasticity also displayed the highest thermal tolerances, reflecting to some extent an evolutionary trade‐off between these two traits. Although our study demonstrates that macroecological climatic niche features measured from species distributions are likely to provide a good approximation of freshwater fish sensitivity to climate change, disentangling the mechanisms underlying both acute and chronic heat tolerances may help to refine predictions regarding climate change‐related range shifts and extinctions.